Role of PD-L1 in Oral Cancer: From the Perspective of Immuno-oncology - Moomal Aslam Khan; Saima Akram Butt (ziauddin University, 2020)
Oral cancers are prevalent in our region and their management requires an upgrade in terms of advanced techniques. Immunotherapy is a novel therapeutic approach across the world that has shown significance in the sphere of oncology. Tumor cells escape detection from the immune surveillance mechanism resulting in proliferation. Through cancer immunotherapy, body's own immune defense mechanism is stimulated with the aid of immunomodulating drugs. Scientists are underway studying the tumor microenvironment where immune editing takes place resulting in tumor escape and evasion. Many immune checkpoint proteins are being studied for clinical implications, however, the immune checkpoint blockade of Programmed death ligand-1(PD-L1) has proven to be successful and FDA approved in certain tumors. Role of increased expression of PD-L1 in oral cancer has been explored with variable results. Most researches have related it with tumor progression and prognosis. This review focuses on the importance of PD-L1 as an emerging immune checkpoint inhibitor, emphasizing its expression in cancers, particularly in oral cancer. The information was retrieved from reliable search engines e.g. PubMed, Medline, Google scholar and others, through original research papers and reviews published hitherto, from 2010-2019. It is essential to explore advanced treatment modalities for oral cancer especially via immunotherapy. Furthermore, additional studies on PD-L1 expression in OSCC are required including standardized protocols to reach definitive conclusions for clinical implications.